Design and development of smart car parking system using arduino and android - Chang, Jian Fei (2015)
In Malaysia, there are too many shopping complex and every shopping complex also has own car park. Somehow they have the similarity which is the car parking system is not complete yet. One of the major problem is the driver have to patrolling around to search for empty car park. This is very wastes of time and fuel. Therefore, the thesis will explain how to improve the existing car parking system to reduce the pain of wasting time and fuel. The system consists of few sub system one of them is the smart management in car parking lot. The driver will get to know where is the empty car park that shown in the LCD at the entrance. Besides that, the security of a car park is very important too. In the system, there is a design and development of a spike system to protect the car. The spike will be activated once the car is parked. Due to the traditional car parking system normally are two color LED which is green and red. Green represent available and red stand for occupied. In the system, it is added a new blue LED to indicate the driver is going to leave the car park soon. Moreover, the blue color light can act as to give direction to the driver where they have park the car. Moreover, there is a little enhancement in the payment system, the driver can make the payment through android app but this system is conceptual due to using the connectivity of Bluetooth. Therefore, it has it limitation. This system can be improve more using web based or PHP base. So this method is indirectly help the driver get to their car fast and easy. Hence, this system can be applied to most of the car park.